2014
DOI: 10.5812/ircmj.9684
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dietary Patterns and Dental Health in Type I Diabetic Children Compared With Healthy Controls

Abstract: Background:Dietary habits are established in childhood and will persist until adulthood, being one of the human health pillars. Many diseases of humans have roots in the individuals’ diet, of which dental caries are one of the common infectious diseases. Diabetes Mellitus is also considered as the most common metabolic disorder in children.Objectives:The purpose of this study was to compare the dietary patterns of children with type I Diabetes Mellitus with that of non-diabetic children, in relation to dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 10 publications
2
11
3
6
Order By: Relevance
“…A cross sectional and questionnaire type of study that showed no difference in dental caries among children with DM1 attributed it to snacking of foods that are protective against dental caries . In this study, diabetic children did not differ significantly from the control group with regard to dental caries status as opposed to the usual scenario where diabetic children are expected to have much more carious lesions.…”
Section: Discussioncontrasting
confidence: 52%
“…A cross sectional and questionnaire type of study that showed no difference in dental caries among children with DM1 attributed it to snacking of foods that are protective against dental caries . In this study, diabetic children did not differ significantly from the control group with regard to dental caries status as opposed to the usual scenario where diabetic children are expected to have much more carious lesions.…”
Section: Discussioncontrasting
confidence: 52%
“…Eleven studies reported a DMFT/DMFS index significantly higher among type 1 diabetics, four found a significantly lower index and 20 did not find statistically significant differences between groups.…”
Section: Resultsmentioning
confidence: 87%
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations